2020
DOI: 10.1371/journal.pone.0242604
|View full text |Cite
|
Sign up to set email alerts
|

“Take the treatment and be brave”: Care experiences of pregnant women with rifampicin-resistant tuberculosis

Abstract: Background There are few data on the on the care experiences of pregnant women with rifampicin-resistant TB. Objective To describe the treatment journeys of pregnant women with RR-TB—including how their care experiences shape their identities—and identify areas in which tailored interventions are needed. Methods In this qualitative study in-depth interviews were conducted among a convenience sample from a population of pregnant women receiving treatment for RR-TB. This paper follows COREQ guidelines. A the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Many pregnant people report feeling isolated and stigmatized when they find out they have TB, something that is often inadvertently perpetuated by healthcare providers. 8 Even sympathetic providers may exacerbate feelings of anxiety and depression if they convey that ‘little is known’ about the risks of TB treatment during pregnancy. Although it is important to be honest when communicating the lack of high-quality data from large populations of pregnant people undergoing TB treatment, providers can be reassuring and supportive.…”
Section: Best Clinical Practice For Pregnant People With Tbmentioning
confidence: 99%
See 1 more Smart Citation
“…Many pregnant people report feeling isolated and stigmatized when they find out they have TB, something that is often inadvertently perpetuated by healthcare providers. 8 Even sympathetic providers may exacerbate feelings of anxiety and depression if they convey that ‘little is known’ about the risks of TB treatment during pregnancy. Although it is important to be honest when communicating the lack of high-quality data from large populations of pregnant people undergoing TB treatment, providers can be reassuring and supportive.…”
Section: Best Clinical Practice For Pregnant People With Tbmentioning
confidence: 99%
“… 7 The result is that while pregnant people are more likely to become sick from TB, they are less likely to receive high-quality person-centered care, placing them, their children and their families at risk of poor outcomes. 8 …”
mentioning
confidence: 99%
“…2 Studies have shown that pregnant women with DR-TB may be offered substandard care, face a high degree of discrimination both from health care workers and from others in their communities, and are systematically denied access to treatment innovations that have been associated with decreased morbidity and mortality in other populations. 3 Not only do these issues affect the health of the pregnant women but also the lives of their unborn children. Children born to pregnant women with TB are at increased risk of prematurity, hospitalization, and death.…”
mentioning
confidence: 99%
“…2 Studies have shown that pregnant women with DR-TB may be offered substandard care, face a high degree of discrimination both from health care workers and from others in their communities, and are systematically denied access to treatment innovations that have been associated with decreased morbidity and mortality in other populations. 3…”
mentioning
confidence: 99%